STRATEGI PENGELOLAAN BISNIS, PROFIL PERUSAHAAN, DAN TATA KELOLA PERUSAHAAN TERHADAP TARIF PAJAK EFEKTIF UNTUK PERUSAHAAN MANUFAKTUR DI SEKTOR INDUSTRI BARANG KONSUMSI - Jefri, Ulfi; Amyati, Amyati; Sari, Devi Novita (LP2M Universitas Bina Bangsa, 2024)
The purpose of this study is to examine the impact of business strategy, corporate characteristics, and corporate governance on effective tax rates. The sample used in this study is manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) in the 2017-2021 period. The method used is an associative quantitative method with a quantitative approach. The study population consisted of 75 companies, with a sample of 14 companies selected using purposive sampling techniques. This study uses multiple linear regression analysis, and the results show that the research variables Return on Asset (ROA), Leverage, and Company Size based on the results of the SPSS test partially have a significant influence on the dependent variable (effective tax rate) in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2017-2021 period. Meanwhile, the variables of business strategy, institutional ownership, and managerial ownership are based on the results of the SPSS test that partially have no influence on the effective tax rate on manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2017-2021 period. The results of the Fcalculate test (simultaneous) for business strategy variables, return on assets, leverage, company size, institutional ownership and managerial ownership using SPSS version 26 show that Fcalculate > Ftable is 3.311 > 2.25, with a significant value of 0.007 < 0.05 means that business strategy, return on assets, leverage, company size, institutional ownership and managerial ownership have a significant effect on the effective tax rate in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2017-2021